Locally Advanced Unresectable Pancreatic Cancer - Johung, Kimberly L; Saif, Muhammad Wasif; Chang, Bryan W (JOP. Journal of the Pancreas, 2014)
Twenty-five percent of patients with pancreatic cancer present with locally advanced disease that is unresectable, and the treatment strategy for these patients is controversial, with options including chemotherapy alone, concurrent chemoradiation, or induction chemotherapy followed by chemoradiation. Abstracts presented at the 2014 American Society of Clinical Oncology (ASCO) Annual Meeting (#4001, #4126, and #4024) addressed local control, quality of life, and prognostic factors associated with current regimens of induction chemotherapy and subsequent chemoradiation. Image: Design of the GERCOR LAP 07 Study.